0293 The Effect of Sleep Loss on Divergent Thinking using a Remote Associates Task. (25th May 2022) - Vignali, Jonathan; Carlsson, Kajsa; Doty, Tracy Jill; Thomas, Balkin; Burke, Tina
Abstract: Introduction: Sleep loss-induced neurobehavioral deficits are a recognized threat to health, safety, and performance. Sleep loss has previously been shown to differentially impact distinct types of cognitive function, although less is known about the higher-order cognitive function, divergent thinking. Understanding the influence of sleep on divergent thinking can assist in developing targeted strategies to mitigate specific cognitive function impairments. Methods: Eight participants (3M/5F), mean age 27.875y (± 5.5y SD) were studied over the course of 40 days in a crossover design. Participants were randomly assigned to one of two study schedules, with 4 participants in each that alternated the order of sleep restriction and total sleep deprivation. The schedules consisted of a baseline assessment and 6 study phases [sleep extension prior to sleep restriction (10h Time in Bed (TIB)), sleep restriction (6h TIB), recovery following sleep restriction, sleep extension prior to total sleep deprivation (10h TIB), total sleep deprivation (62h), and recovery following sleep restriction. The Remote Associates Task (RAT), a task to assess divergent thinking by presenting a triad of apparently unrelated words with the goal of identifying a unifying 4th word, was administered the evening of the last day of every phase. RAT performance metrics included number of triads attempted, correct responses, repeated trials, and mean correct and incorrect reaction times. Results: No differences were found in total number of word triads attempted by participants (p=0.18). The number of correct responses during baseline was lower than during sleep restriction, recovery from sleep restriction, and total sleep restriction (p=0.00691), most likely reflecting a steep learning curve. No significant main effect of phase was found for any RAT metric. Conclusion: These preliminary findings suggest divergent thought as measured by the RAT is conserved across a differential amounts of sleep. More studies are needed to better characterize the impact of sleep loss on divergent thinking as well as possible mediating effects of other higher-order cognitive functions. Support (If Any): Department of Defense Military Operational Medicine Research Program (MOMRP)